2012
DOI: 10.1002/hbm.21476
|View full text |Cite
|
Sign up to set email alerts
|

Right temporoparietal junction and attentional reorienting

Abstract: The interaction between goal-directed and stimulus-driven attentional control allows humans to rapidly reorient to relevant objects outside the focus of attention--a phenomenon termed contingent reorienting. Neuroimaging studies have observed activation of the ventral and dorsal attentional networks, but specific involvement of each network remains unclear. The present study aimed to determine whether both networks are critical to the processes of top-down contingent reorienting. To this end, we combined the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 55 publications
(100 reference statements)
6
54
1
Order By: Relevance
“…Consequently, our rTPJ site was perhaps linked with spatial attention shifts rather than contingent capture. A recent study by Chang et al (2013) found evidence for the causal involvement of TPJ in contingent capture using stimulation coordinates based on a neuroimaging investigation of contingent capture (Serences et al, 2005). In fact, the rTPJ stimulation site in that study was more ventral than ours, and this may prove to be the critical factor.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Consequently, our rTPJ site was perhaps linked with spatial attention shifts rather than contingent capture. A recent study by Chang et al (2013) found evidence for the causal involvement of TPJ in contingent capture using stimulation coordinates based on a neuroimaging investigation of contingent capture (Serences et al, 2005). In fact, the rTPJ stimulation site in that study was more ventral than ours, and this may prove to be the critical factor.…”
Section: Discussioncontrasting
confidence: 53%
“…Similarly, there is scant evidence for a causal role of the TPJ in contingent capture. However, TMS of right TPJ may influence contingent capture as indexed by behavioral accuracy (Chang et al, 2013). More generally, TMS of TPJadjacent regions affects shifts of spatial attention (Chambers et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, even though the dynamics of dorsal and ventral interaction are still largely unknown (but see Corbetta et al, 2008), there are several TMS studies that support the notion that disruption of the ventral network can indeed influence attentional processes. For example, TMS over TPJ has been shown to have effects on visual extinction , exogenous cueing (Chica et al, 2011), and re-orienting in an attentional capture paradigm (Chang et al, 2013). At present, no strong conclusion can be drawn from this, but it certainly seems promising to further investigate the remote effects of ventral network stimulation on the dorsal network.…”
Section: Competing Models Of Attentional Controlmentioning
confidence: 97%
“…Soutschek et al (2013) addressed stimulus-stimulus conflicts and stimulus-response conflicts as well as conflict adaptation between trials and stimulated the pre-SMA and intraparietal sulcus (IPS)/inferior parietal lobe (IPL). Chang et al (2013) focused on the dorsal and ventral frontoparietal networks, in particular the right FEF and the temporo-parietal junctions (TPJ). The majority of TMS studies though concentrated predominantly on response selection issues.…”
Section: Flanker Paradigmmentioning
confidence: 99%
“…In sum, the study supports the idea of conflict-specific control processes. Chang et al (2013) aimed at assessing the role of the dorsal and ventral frontoparietal networks (Corbetta and Shulman, 2002;Corbetta et al, 2008) in contingent reorienting and to assess the spatial selectivity of the ventral network. Theta burst TMS was applied over the right FEF (rFEF; dorsal), right TPJ (rTPJ, ventral) and the left TPJ (lTPJ).…”
Section: Perception Attention and Response Conflictmentioning
confidence: 99%